The Borax Analysis Of The Crackers At Blauran Market, Salatiga City - Palimbong, Sarlina; Sihombing, Monang; Mulyanto, Milka Meliana (Jurnal Penelitian Pertanian Terapan, 2024)
Misuse of chemicals, such as borax, as an additive in food is still common. This abuse is intended to increase elasticity and crispiness for longer in food products, even though borax is prohibited in the food industry. Some food products on the market that often contain borax are tofu, meatballs, noodles, and crackers. Research studies and mass media in several traditional markets in Indonesia have proven and verified the presence of borax in crackers. Based on this, we want to know whether there is the same thing in the distribution of crackers at Blauran Market, Salatiga City. Therefore, this research aims to quantitatively determine the status of borax in crackers sold at Blauran Market, Salatiga City, in 2023—a quantitative descriptive research method. Sampling used the purposive sampling method. The research design used was a completely randomised factorial design. The first factor is the type of cracker, consisting of four levels: gendar cracker brand X, gendar cracker brand Y, white eggplant cracker brand minute. Each treatment combination was repeated three times to obtain 24 experimental units. Quantitative test of samples using a UV-VIS spectrophotometer. Data processing using two-factor ANOVA with replication. The test results showed that the four brands of cracker samples contained >100 ppm borax. The highest borax content was in white eggplant crackers.